2018
DOI: 10.1177/0269215518758484
|View full text |Cite
|
Sign up to set email alerts
|

Goal setting in paediatric rehabilitation for children with motor disabilities: a scoping review

Abstract: The results highlight significant gaps in the literature explicating a sound theoretical basis for goal setting in paediatric rehabilitation and research evaluating the effects of goal qualities and goal setting processes on the achievement of meaningful outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 87 publications
(348 reference statements)
1
75
0
Order By: Relevance
“…Decision-making in pediatric rehabilitation is especially evident in goal-setting processes where collaborative dialogue and power sharing occurs [ 6 ], and during which clients and professionals make decisions and agree on goals [ 23 ]. From a scoping review of 62 studies of goal-setting in children’s rehabilitation, researchers identified that carers and teachers have been the main stakeholders, while the conspicuous absence of children in the process was noted [ 24 ]. While some evidence shows positive outcomes for goal attainment, and increased motivation of the child when child-centred goal-setting is implemented, conversely also the lack of child determined goals was noted as possibly contributing to a lack of motivation to achieve goals [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decision-making in pediatric rehabilitation is especially evident in goal-setting processes where collaborative dialogue and power sharing occurs [ 6 ], and during which clients and professionals make decisions and agree on goals [ 23 ]. From a scoping review of 62 studies of goal-setting in children’s rehabilitation, researchers identified that carers and teachers have been the main stakeholders, while the conspicuous absence of children in the process was noted [ 24 ]. While some evidence shows positive outcomes for goal attainment, and increased motivation of the child when child-centred goal-setting is implemented, conversely also the lack of child determined goals was noted as possibly contributing to a lack of motivation to achieve goals [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested self-determination theory (SDT) as a framework for health care practitioners to use to focus on the quality and quantity of a client's motivation to improve intervention and outcomes (Meyns et al, 2018;Pritchard-Wiart & Phelan, 2018;Ziviani, 2015). In support, Bulanda and McCrea (2013) found incorporating SDT principles into programing produced positive results and engagement for adolescents of poverty.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of mobility and self-care, including the independence level, are usually examined only in relation to gross motor abilities or in relation to gross motor and fine manual abilities [5,[8][9][10][11][12]. Besides, the effects of different types of treatment were examined and the factors influencing the development of functional independence in children with CP identified [6,7,13,14]. In other words, DOI: https://doi.org/10.2298/SARH190321077M previous empirical research did not take into account the overall profile of motor abilities of children with CP that, in addition to both gross motor function and manual abilities, includes bimanual fine motor function.…”
Section: Introductionmentioning
confidence: 99%